2016
DOI: 10.1186/s41256-016-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to low uptake and renewal of health insurance: a qualitative study in Ghana

Abstract: BackgroundThe effort to expand access to healthcare and reduce health inequalities in many low income countries have meant that many have adopted different levels of social health protection mechanisms. Ghana introduced a National Health Insurance Scheme (NHIS) in 2005 with the aim of removing previous barriers created by the user fees financing system. Although the NHIS has made health accessible to some category of people, the majority of Ghanaians (60 %) are not enroled on the scheme. Earlier studies have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 21 publications
6
79
2
Order By: Relevance
“…Our study findings of less expenditure on the insured compared to the uninsured is consistent with findings of some studies conducted in Ghana where the uninsured paid more for malaria care than the insured [ 14 , 38 , 39 ]. However, enrolment of households into the NHIS is not encouraging given that as at 2016, only 40% of Ghanaians were enrolled into the scheme with valid membership cards [ 40 ]. It has been reported that the main reason for low enrolment into the NHIS is affordability of the premium and poor households are less covered [ 30 , 41 45 ].Therefore, innovative methods are required to improve enrolment into the NHIS, especially the poor and vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings of less expenditure on the insured compared to the uninsured is consistent with findings of some studies conducted in Ghana where the uninsured paid more for malaria care than the insured [ 14 , 38 , 39 ]. However, enrolment of households into the NHIS is not encouraging given that as at 2016, only 40% of Ghanaians were enrolled into the scheme with valid membership cards [ 40 ]. It has been reported that the main reason for low enrolment into the NHIS is affordability of the premium and poor households are less covered [ 30 , 41 45 ].Therefore, innovative methods are required to improve enrolment into the NHIS, especially the poor and vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of the quality of care at health facilities and perception of the NHIS are significant factors to enrolment. Some insured patients, do complain of poor quality of health services provided at the health facilities which include long waiting times, bad attitude by health facility staff, and drug shortages [31, 49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The coverage ratio measures proportion of the target population participating in the programme, serving as a key indicator of marketing effectiveness and programme’s success [ 33 ]. The marketing effectiveness, however depends largely on client’s satisfaction with the services and the perceived value of the programme [ 30 , 33 – 36 ]. Voluntary enrolment of large proportion of the target population, particularly in SHI programmes, gives an indication of acceptance of the risk-pooling concept and understanding of the programme including how to access the benefits.…”
Section: Introductionmentioning
confidence: 99%